2019
DOI: 10.1186/s12889-019-8070-9
|View full text |Cite
|
Sign up to set email alerts
|

Associations between dietary patterns and 10-year cardiovascular disease risk score levels among Chinese coal miners——a cross-sectional study

Abstract: BackgroundDiet-related cardiovascular diseases have produced a large health burden in China. Coal miners are a high-risk population for cardiovascular disease, but there is little evidence concerning associations between coal miners’ dietary patterns and their 10-year cardiovascular disease risk score levels.MethodsThe study included 2632 participants and focused on dietary patterns associated with higher 10-year cardiovascular disease risk score levels. A valid semi-quantitative food frequency questionnaire w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 54 publications
1
8
0
Order By: Relevance
“…And the rate of CVD death was ~ 3 times higher in lower-and middle-income countries compared to those with high-incomes [3]. Diet plays an important role in preventing CVD [4]. It has been suggested that adherence to a healthy diet reduces the risk of cardiovascular disease by 80-90% [5].…”
Section: Introductionmentioning
confidence: 99%
“…And the rate of CVD death was ~ 3 times higher in lower-and middle-income countries compared to those with high-incomes [3]. Diet plays an important role in preventing CVD [4]. It has been suggested that adherence to a healthy diet reduces the risk of cardiovascular disease by 80-90% [5].…”
Section: Introductionmentioning
confidence: 99%
“…First, only healthy coal miners were recruited, which makes this study not generalizable to all coal mine workers. Previous studies reported that the prolonged mining work may cause lung diseases (pneumoconiosis and silicosis), cardiopulmonary function injury and cardiovascular disease among mining workers [ 7 , 8 , 9 , 10 ]. Future epidemiological study should provide adequate insights to the field of industrial medicine, relating to occupational diseases such as coronary artery and lung diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Underground mining can present health risks to workers due to poor ventilation and dustiness [ 5 , 6 ]. These might be the reasons behind the high and increasing annual rates of coal-mining occupational health problems such as lung diseases (pneumoconiosis and silicosis), cardiopulmonary function injury and cardiovascular disease among mining workers [ 7 , 8 , 9 , 10 ]. In addition, underground miners usually work in high-humidity and high-temperature environments, which present additional risks to the cardiopulmonary functions [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Benefited from the poverty alleviation work in recent years, these areas have achieved impressive economic developments. In the former case, changes in lifestyle and diet often come with rapid economic developments [ 34 , 35 ]. A longitudinal study in China showed that between 1995 and 2014 stunting, thinness continued to reduce in school-aged children and adolescents while the prevalence of obesity markedly increased [ 36 ].…”
Section: Discussionmentioning
confidence: 99%